Women from afar: an observational study of demographic characteristics and mortality among foreign‐born women living with HIV in the Women's Interagency HIV Study (WIHS) in the United States 1994‐2016. Issue 5 (21st May 2020) - Adedimeji, Adebola; Shi, Qiuhu; Haddad, Lisa; Holman, Susan; Edmonds, Andrew; Weber, Kathleen; Kassaye, Seble; Karim, Roksana; Bolivar, Hector; Reid, Michael; Kempf, Mirjam‐Colette; Golub, Elizabeth; et al.
Abstract: Introduction: Foreign‐born persons comprise ~13% of the US population. Immigrants, especially women, often face a complex set of social and structural factors that negatively impact health outcomes including greater risk of HIV infection. We described socio‐demographic, clinical and immunological characteristics and AIDs and non‐AIDS death among foreign‐born women living with HIV (FBWLWH) participating in the US Women's Interagency HIV Study (WIHS) in the US from 1994 to 2016. We hypothesized that FBW will experience higher AIDS‐related mortality compared to US‐born women (USBW). Methods: The WIHS is a multicenter prospective observational cohort study of mostly women living with HIV (WLWH). The primary exposure in this analysis, which focused on 3626 WLWH, was self‐reported country of birth collapsed into foreign‐born and US born. We assessed the association of birthplace with categorized demographic, clinical and immunological characteristics, and AIDS/non‐AIDS mortality of WLWH, using chi‐squared tests. Proportional hazard models examined the association of birthplace with time from enrolment to AIDS and non‐AIDS death. Results: Of the 628 FBW, 13% were born in Africa, 29% in the Caribbean and 49% in Latin America. We observed significant differences by HIV status in socio‐demographic, clinical and immunological characteristics and mortality. For both AIDS and non‐AIDS caused deaths FBW WLWH had lower rates of death. Adjusting for year of study enrolment and other demographic/clinical characteristics mitigated FBW's statistical survival advantage in AIDS deaths Relative Hazard (RH = 0.91 p  = 0.53), but did not substantively change the survival advantage in non‐AIDS deaths RH = 0.33, p  < 0.0001). Conclusion: Foreign‐born WLWH exhibited demographic, clinical and immunological characteristics that are significantly different compared with women born in the US or US territory. After adjusting for these characteristics, the FB WLWH had a significantly lower hazard of non‐AIDS but not AIDS mortality compared to women born in the US or a US territory. These findings of non‐increased mortality can help inform models of care to optimize treatment outcomes among FBWLWH in the United States.